A heart full of headstones [large type] - Rankin, Ian (Rankin, Ian. Inspector Rebus novel series, 2023)
"John Rebus stands on trial for a crime that could put him behind bars for the rest of his life. But what drove a good man to cross the line? Detective Inspector Siobhan Clarke may well find out. Clarke is tasked with the city's most explosive case in years, an infamous cop has gone missing. Finding him will expose not only her superiors, but her mentor John Rebus. And Rebus himself may not have her own interests at heart, as the repayment of a past debt places him in the crosshairs of both crime lords and his police brethren. One way or another, a reckoning is coming--and John Rebus may be hearing the call for last orders"--